EFFECT OF PROPAGATION METHODS, SPRAY WITH PACLOBUTRAZOL AND MICRONUTRIENT ON GROWTH OF - A. O. AL - Atrakchii (Mesopotamia Journal of Agriculture)
This study was carried on Dahlia hybrida cv. Edinburgh, to compare two propagation methods, application of paclobutrazol PBZ at 0, 10 and 20 mg/liter and micronutrients at concentrations 0.00, 0.25 and 0.50 g/liter on vegetative growth. The results can be summarized as follows: Plants propagated by cuttings gave best results for flowering time and inflorescence stalk while plants propagated by tuberous roots gave best results of inflorescence number and inflorescence diameter. Plants sprayed with 10, 20 mg/liter PBZ gave best results of flowering time in the second season and inflorescence diameter in first season. Spraying plants with micronutrient at concentration 0.50 g/liter gave best results of inflorescence number and diameter. In general, plants propagated by cuttings treated with any concentrations of PBZ and micronutrients gave best results of flowering time, but the largest number of inflorescences/plant 12.88 obtained when plants propagates by tuberous roots were treated with 20 mg PBZ/liter and 0.50 g/liter micronutrients in first season, but the largest number 6.77 inflorescences/plant obtained in the second season when plants werenot treated with PBZ.